Enhanced Photovoltaic Performance of Amorphous Donor–Acceptor Copolymers Based on Fluorine‐Substituted Benzodioxocyclohexene‐Annelated Thiophene. Issue 13 (23rd January 2018) - Ie, Yutaka; Morikawa, Koki; Zajaczkowski, Wojciech; Pisula, Wojciech; Kotadiya, Naresh B.; Wetzelaer, Gert‐Jan A. H.; Blom, Paul W. M.; Aso, Yoshio
Abstract: Donor–acceptor (D‐A) type π‐conjugated copolymers with crystalline behavior have been extensively investigated as donor semiconductors in organic photovoltaics (OPVs). On the other hand, the development of high‐performance amorphous donor materials is still behind. The amorphous donor copolymerDTS‐C0 (F2 ) consisting of dithieno[3, 2‐ b :2′, 3′‐ d ]silole (DTS ) donor unit and the recently developed fluorine‐substituted naphtho[2, 3‐ c ]thiophene‐4, 9‐dione (C0 (F2 ) ) acceptor unit shows moderate photovoltaic performance upon blending with PC71 BM. In this work, to enhance the hole‐transporting characteristics, a 3‐hexylthiophene (HT ) spacer unit is integrated into the conjugated backbone, resulting in a new amorphous copolymerDTS‐HT‐C0 (F2 ) . The strong electron‐accepting nature ofC0 (F2 ) allows the introduction of theHT spacer without affecting the frontier orbital energies and thus the D‐A character. Without using solvent additives and thermal annealing, OPVs based onDTS‐HT‐C0 (F2 ) and [6, 6]‐phenyl‐C71‐butyric acid methyl ester PC71 BM show an improved power conversion efficiency of 9.12%. Investigation of the device physics unambiguously reveals that the hole mobility of the copolymer in the blend is increased by an order of magnitude by the introduction ofHT, while keeping an amorphous film nature, leading to higher short‐circuit current density and fill factor. These results demonstrate the realization of high‐performance OPVs based on amorphous active layers. Abstract : Donor–acceptor type π‐conjugated copolymer based on fluorine‐substituted naphtho[2, 3‐ c ]thiophene‐4, 9‐dione is developed for an amorphous donor material in organic photovoltaics . Bulk‐heterojunction solar cells using the blend film of synthesized copolymer and PC71 BM as an acceptor show photovoltaic characteristics with power conversion efficiencies of 9.12%. Blend‐film investigation reveals that this high performance comes from the increased hole‐transporting nature of the copolymer.